KNOWLEDGE MANAGEMENT IMPLEMENTATION STRATEGY IN ORGANIZATION DEPARTMENT OF PT X - Efrata, Lidya Chrisnawaty; Tjakraatmadja, Jann Hidajat (Journal of Business and Management, 2018)
Abstract. PT X is being intense in product Y market launch and it requires preparation of employee in maintaining, improving and implementing knowledge through a good organizational knowledge system, thus within Organization Department. Current condition of Organization Department has no systematic system that can integrating all the human resources plan. Therefore Organization Department needs a Knowledge Management (KM) to integrate human resources partial system into human resources complex system. Knowledge management implementation strategy (pull system) model adopted for this qualitative study. The finding of this study, there will be some improving system or even a new system in human resources by finds the critical knowledge to produce developing integrated knowledge management system. Thus, Organization department must have Knowledge management (KM) strategy and initiative to reforming people, process and Information and Technology (IT), this process occurs with a revitalization that starts from the leader's commitment until completed the establishment of a knowledge center. In addition, the impact of this study will lead Organization Department to building a systematic and effective system of human resources management toward product Y market launch.Â Keywords:Â  Critical Knowledge, Human Resources Complex System, Integrated Knowledge Management System, Knowledge Managemet (KM), Pull System